1950
DOI: 10.1172/jci102335
|View full text |Cite
|
Sign up to set email alerts
|

Plasma and Red Cell Iron Turnover in Normal Subjects and in Patients Having Various Hematopoietic Disorders 1

Abstract: One of the obvious uses which may be made of a tracer in biological studies is the determination of rates. Zilversmitt and associates (1) and more recently London (2) have called attention to this use of a tracer. Only when the isotope can be added without effectively changing the amount or concentration of material in a steady state system can such an application be made. Not until recently has radio iron been available which had sufficiently high specific activity to tag plasma iron without changing its conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
75
0
3

Year Published

1950
1950
1961
1961

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 325 publications
(84 citation statements)
references
References 19 publications
6
75
0
3
Order By: Relevance
“…Salt Lake City) (Received for publication, October 3, 1955) In the preceding publication (1) the results of studies on the kinetics of iron metabolism (2)(3)(4)(5) in normal growing swine were reported. The purpose of this paper is to present the results of similar studies in swine with three different types of experimentally induced anemias.…”
Section: (From the Department Of Medicine College Of Medicine Univementioning
confidence: 99%
“…Salt Lake City) (Received for publication, October 3, 1955) In the preceding publication (1) the results of studies on the kinetics of iron metabolism (2)(3)(4)(5) in normal growing swine were reported. The purpose of this paper is to present the results of similar studies in swine with three different types of experimentally induced anemias.…”
Section: (From the Department Of Medicine College Of Medicine Univementioning
confidence: 99%
“…
The availability of radioactive iron (Fe 6~) of high specific activity and the development of the scintillation counter enabled Huff et al (1) to devise a technique for determining the turnover rates of iron through plasma and red cells.This method involves the intravenous injection of a tracer dose of Fe s9 containing a quantity of carrier iron sufficiently small that the plasma iron concentration will not be elevated measurably. The Fe s9 radioactivity disappears from the plasma according to the equation of a first order reaction and the time at which half of the injected dose has disappeared from the plasma (T~) is determined by plotting the counts of serial plasma samples on semilogarithmic paper.
…”
mentioning
confidence: 99%
“…The availability of radioactive iron (Fe 6~) of high specific activity and the development of the scintillation counter enabled Huff et al (1) to devise a technique for determining the turnover rates of iron through plasma and red cells.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…
The utilization of radioactive iron to evaluate erythropoietic function in normal and disease states in man is well established (1)(2)(3)(4)(5)(6)(7)(8). These studies have demonstrated that the half-time (Ti) of plasma radioiron disappearance and the red cell uptake of radioactive iron are valid parameters of bone marrow function.
…”
mentioning
confidence: 99%